Exploring the views of healthcare practitioners on postnatal mental illness screening among Malaysian women - Mohd Arifin, Siti Roshaidai; Daud, Siti Aishah; Ruslan, Nur Liyana Shahmi; Abang Abdullah, Khadijah Hasanah; Abas, Nurul Ain Hidayah; Husain, Rohayah; Abd Aziz, karimah hanim; Musa, Ramli; Syed Mohideen, Fathima Begum; Perveen, Asma; Che Mat, Khairi; Idris, Izazol (UPM Press, 2022)
Introduction: Healthcare practitioners involved in the maternity care provision should be equipped with adequate knowledge and skills in the screening of postnatal mental illness. The promotion of a screening tool for this purpose can enhance these skills among the healthcare providers. In Malaysia, there is a lack of fundamental knowledge among healthcare practitioners regarding postnatal mental illness and their perceptions are not fully understood, thus hindering the development of relevant screening tools. This study aimed to explore the views of Malaysian healthcare practitioners on the indicators and potential mechanisms for the screening of postnatal mental illness. Method: This qualitative study was conducted using semi-structured interviews involving 28 healthcare practitioners at maternal and child health clinics, psychiatric departments, and obstetrics and gynaecology departments across 18 maternal and child health clinics and six government hospitals in the states of Pahang, Terengganu, Perak, Negeri Sembilan, and Kuala Lumpur. The data were analysed using framework analysis. Results: The healthcare practitioners’ views on postnatal mental illness were reflected in three themes, namely perceived causes of postnatal mental illness, indicators of postnatal mental illness, as well as screening and intervention mechanisms for postnatal mental illness. According to the respondents, the existing screening tools available within the clinical practice were less sensitive in assessing postnatal mental illness. Conclusion: The introduction of a relevant screening tool in addressing the common symptoms of postnatal mental illness can improve its the detection among Malaysian women.